2018
DOI: 10.1089/thy.2017.0600
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Serum Thyrotropin Concentrations Observed from Big Data Obtained During Six Consecutive Years from 2010 to 2015 at a Single Hospital in Japan

Abstract: The fact that the TSH concentrations show annual changes in areas where the temperature ranges during the year are rather wide should be borne in mind for interpretation of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
6
18
0
Order By: Relevance
“…For median TSH values, this was more heterogeneous. The median TSH value was similar to that found in the NHANES III cohort and the study reported by Yoshihara et al in Japan [2,15], but lower than in studies conducted in Spain and China [16,17]. This might be related to the age of the patients included and also to the iodine status of the population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For median TSH values, this was more heterogeneous. The median TSH value was similar to that found in the NHANES III cohort and the study reported by Yoshihara et al in Japan [2,15], but lower than in studies conducted in Spain and China [16,17]. This might be related to the age of the patients included and also to the iodine status of the population.…”
Section: Discussionsupporting
confidence: 87%
“…Yoshihara et al [15] found a relationship between TSH and daily temperatures represented by months of the year. They studied TSH values obtained from a single center for six consecutive years and measured with a single analytic method.…”
Section: Discussionmentioning
confidence: 98%
“…In adults, TSH hypersecretion secondary to low ambient temperatures has indeed been reported in patients with primary hypothyroidism on constant replacement dosage of thyroxine (31). Recently, Yoshihara et al (32) reported seasonal changes in TSH in 135,417 Japanese adult patients and a negative correlation between TSH and daily temperature. Another possible explanation is the relationship between maternal vitamin D and fetal TSH levels.…”
Section: Discussionmentioning
confidence: 94%
“…In a study involving euthyroid and SCH subjects in Korea [19] the serum TSH increased during the winter and spring seasons leading to transition to SCH. And a study conducted for six years in Japan, another country with a temperate climate, reported a decreased TSH concentration during summer that got reversed in winter; there existed a negative correlation between the daily temperatures and TSH and FT3 concentrations [27]. But these two studies [19, 27] had a shortcoming; the entire study, i.e., the follow-up, was not carried out on the same subjects.…”
Section: Discussionmentioning
confidence: 99%
“…And a study conducted for six years in Japan, another country with a temperate climate, reported a decreased TSH concentration during summer that got reversed in winter; there existed a negative correlation between the daily temperatures and TSH and FT3 concentrations [27]. But these two studies [19, 27] had a shortcoming; the entire study, i.e., the follow-up, was not carried out on the same subjects. The subjects who developed thyroid disease or were on thyroid treatment throughout the study could not be excluded because the studies were carried out retrospectively.…”
Section: Discussionmentioning
confidence: 99%